Development strategies, macroeconomic policies, and the agricultural sector in Zambia - Resnick, Danielle; Thurlow, James (Cornell University, 2008)
At its independence in 1964, Zambia, a landlocked country in Southern Africa, was perceived to have a bright future. The country was endowed with vast natural resources, including favorable agroecological conditions and large copper deposits. Within two decades, however, the country descended into a macroeconomic crisis. Agriculture and rural incomes stagnated and industry was collapsing, leading to severe poverty and malnutrition. This case study examines how Zambia’s different development strategies led first to a macroeconomic crisis in the 1980s and then to economic recovery in the late 1990s. More specifically, it focuses on the interplay between macroeconomic and sectoral policies and draws attention to how policies and stakeholder interests at different levels of an economy must work synergistically if a development strategy is to be sustainable and achieve its objectives. Zambia’s government first adopted a strategy of state-directed industrialization. Bolstered by copper revenues and the political influence of urban dwellers, this strategy favored urban industry over agriculture and rural development. When world copper prices collapsed, however, the country plunged into macroeconomic crisis and the sectoral policies underlying state-directed industrialization became unsustainable. Driven by pressures from domestic political constituents and international donors, Zambia became a multiparty democracy in 1991 and elected a government that favored a strategy of market-driven development. The country eventually achieved macroeconomic stability by curtailing sectoral investments and subsidies, but with mixed consequences for national welfare and agricultural producers. Zambia has recently experienced a period of renewed growth and poverty reduction. Yet just as falling copper prices forced Zambia to undergo market-oriented reforms, the recent boom in world copper prices could provide incentives to return to a more interventionist development strategy. To implement such a strategy, however, the government would have to raise taxes on foreign mining companies, which now own Zambia’s previously state-owned mines. This case study focuses on trade-offs from raising mining taxes and possible implications for agriculture and the food system. Given the current political environment and taking into account the mechanisms through which a change in world copper prices affects the agricultural sector, your assignment is to advise Zambia’s government on how it might use the revenues gained from increasing mining taxes to improve economic growth and reduce poverty.